Kidney Disease Measures and Left Ventricular Structure and Function: The Atherosclerosis Risk in Communities Study - Kunihiro Matsushita; Lucia Kwak; Yingying Sang; Shoshana H. Ballew; Hicham Skali; Amil M. Shah; Josef Coresh; Scott Solomon (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2017)
BackgroundHeart failure is one of the most important complications of chronic kidney disease (CKD). However, few studies comprehensively investigated left ventricular (LV) structure and function in relation to 2 key CKD measures, estimated glomerular filtration rate (eGFR) and urine albumin/creatinine ratio (ACR). Methods and ResultsAmong 4175 ARIC (Atherosclerosis Risk in Communities) participants (aged 66–90 years during 2011–2013), we quantified the association of eGFR and ACR with echocardiogram parameters of LV mass, size, systolic function, and diastolic function. Adjusting for demographic variables, both CKD measures were significantly associated with most echocardiogram parameters. Additionally accounting for other potential confounders, we observed significantly higher LV mass index according to reduced eGFR (82.3 [95% confidence interval (CI), 77.6–87.0] g/m2 for eGFR <30 mL/min per 1.73 m2, 80.9 [95% CI, 77.3–84.6] g/m2 for eGFR 30–44 mL/min per 1.73 m2, and 80.1 [95% CI, 76.7–83.5] g/m2 for eGFR 45–59 mL/min per 1.73 m2 compared with 78.7 [95% CI, 75.3–82.1] g/m2 for eGFR 75–89 mL/min per 1.73 m2; trend P<0.001). Regarding LV size and function, significant differences were observed for some parameters, particularly at eGFR <30 mL/min per 1.73 m2. For ACR, the associations remained significant for most parameters (eg, LV mass index, 91.5 [95% CI, 86.6–96.5] g/m2 for ACR ≥300 mg/g and 82.9 [95% CI, 79.4–86.3] g/m2 for ACR 30–299 mg/g compared with 77.7 [95% CI, 74.4–81.1] g/m2 for ACR <10 mg/g [trend P<0.001]; left arterial volume index, 24.9 [95% CI, 22.9–26.8] and 24.7 [95% CI, 23.4–26.1] mL/m2 compared with 23.4 [95% CI, 22.1–24.7] mL/m2, respectively [trend P=0.010]). Dichotomizing echo parameters with clinical thresholds, the stronger relationships of ACR over eGFR were further evident. ConclusionsLV mass was related to both CKD measures, whereas LV size and function were robustly associated with albuminuria. These results have implications for pathophysiological processes behind cardiorenal syndrome and targeted cardiac assessment in patients with CKD.